Multifungsi Fi'l al-Amr dalam Hadis Keluarga dan Konteks Relasi Sosial: Kajian Balaghah dan Pragmatik - Kartini (Universitas Islam Negeri Palopo, 2025)
This study investigates the pragmatic and rhetorical functions of imperative forms (fi'l al-amr) in Prophetic hadiths within family and social relational contexts. Imperative constructions are traditionally associated with command; however, their actual usage in hadith discourse reveals significant functional variability. Using a qualitative integrative design, 13 hadiths were selected purposively from five canonical collections (Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Sunan Abī Dāwūd, Sunan Ibn Mājah, and Musnad Aḥmad) and analysed through two complementary frameworks: Speech Act Theory (Austin, 1962; Searle, 1969) and classical Arabic rhetoric (balāghah), specifically ʿilm al-maʿānī. The findings identify six pragmatic functions—advisory, moral obligation, instructional, social regulation, facilitative, and social responsibility—distributed across three relational domains: spousal, parent–child, and family–community relations. Rhetorical analysis categorises these forms into six balāghah functions: al-naṣḥ, al-irshād, al-ilzām, al-taḥdhīr, al-ilzām al-ijtimāʿī, and al-ilzām al-masyrūṭ. The study demonstrates significant convergence between the two frameworks, confirming that classical Arabic rhetorical theory anticipates key insights of modern pragmatics. These findings contribute a new concept of relational domain calibration to Speech Act Theory and offer a pedagogical model for context-sensitive interpretation of directive language in Islamic texts. Penelitian ini mengkaji fungsi pragmatik dan retorika bentuk imperatif (fi'l al-amr) dalam hadis Nabi yang bertemakan relasi keluarga dan sosial. Bentuk imperatif secara tradisional diidentikkan dengan perintah; namun dalam wacana hadis, penggunaannya menunjukkan variabilitas fungsi yang signifikan. Menggunakan desain kualitatif integratif, 13 hadis dipilih secara purposif dari lima koleksi kanonik dan dianalisis melalui dua kerangka komplementer: Speech Act Theory (Austin, 1962; Searle, 1969) dan retorika Arab klasik (balāghah), khususnya cabang ʿilm al-maʿānī. Hasil penelitian mengidentifikasi enam fungsi pragmatik—nasihat, kewajiban moral, instruksional, regulasi sosial, fasilitatif, dan tanggung jawab sosial—yang terdistribusi dalam tiga domain relasional: suami–istri, orang tua–anak, dan relasi keluarga–komunitas. Analisis balāghah mengkategorikan bentuk-bentuk tersebut ke dalam enam fungsi: al-naṣḥ, al-irshād, al-ilzām, al-taḥdhīr, al-ilzām al-ijtimāʿī, dan al-ilzām al-masyrūṭ. Penelitian ini menunjukkan konvergensi signifikan antara dua kerangka tersebut dan mengusulkan konsep relational domain calibration sebagai pelengkap Speech Act Theory, sekaligus menawarkan model pedagogis interpretasi bahasa direktif dalam teks Islam.